Changes in the Tradition of Islamic Studies at Pesantren: A Grounded Theory Approach - Khoiriyah Khoiriyah; Ahmad Ali Riyadi (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2023)
Pesantren has a distinctive Islamic scientific tradition, namely the kitab kuning tradition. However, now a phenomenon exists where kitab kuning is no longer used. This study aimed to explore changes in the habit of Islamic studies at Pesantren Assalaam. This research used a case study qualitative research at Pesantren Assalaam, Sukoharjo, Indonesia. There were 18 respondents consisting of 10 teachers, 4 pesantren administrators and 4 employees. Observations, interviews, and documentation are used to collect data. The main findings of this study revealed that modernization led to a change in the tradition of Islamic studies, which was marked by the absence of kitab kuning in the pesantren curriculum as a learning reference authority. The white book references were used as the typical tradition of developed Islamic studies at Pesantren Assalaam. The white book summarized several kitab kuning that can be evaluated each semester, printed on white paper.